Baccaurea angulata fruit inhibits lipid peroxidation and induces the increase in antioxidant enzyme activities - Mikail, Maryam Abimbola; Ahmed, Idris Adewale; Ibrahim, Muhammad; Hazali, Norazlanshan; Abdull Rasad, Mohammad Syaiful Bahari; Abdul Ghani, Radiah; Hashim, Ridzwan; Abdul Wahab, Ridhwan; Arief Ichwan, Solachuddin Jauhari; Md Isa, Muhammad Lokman; Draman, Samsul; Adros Yahya, Mohammad Noor (Springer, 2016)
Purpose: The consequence of the increased demand due to the population expansion has put tremendous pressure on the natural supply of fruits. Hence, there is an unprecedented growing interest in the exploration of the potentials of underutilized fruits as alternatives to the commercially available fruits. Baccaurea angulata is an underutilized fruit widely distributed in Borneo Island of Malaysia. The present study was conducted to investigate the effects of B. angulata whole fruit (WF), skin (SK) and pulp (PL) juices on malondialdehyde (MDA) levels and antioxidant enzymes in rabbits fed high-cholesterol diet.Methods: Thirty-six male rabbits of New Zealand strain were randomly assigned to six groups. Rabbits were fed either a standard pellet (group NC) or a high-cholesterol diet (groups HC, PC, WF, SK and PL). Groups WF, SK and PL were also given 1 ml/kg/day B. angulata WF, SK and PL juices, respectively. Results: Baccaurea angulata had high antioxidant activities. The administration of the various juices significantly reduced (p < 0.05) the concentration of induced plasma MDA. The decrease in the SOD, GPx, CAT and TAC levels caused by cholesterol feeding was also ameliorated with B. angulata. Conclusion: Our results show that B. angulata fruit is beneficial in positively influencing and managing oxidative damage.